Epidemiology of college athlete sizes, 1950s to current - Yamamoto, J. B.; Yamamoto, B. E.; Yamamoto, P. P.; Yamamoto, L. G. (Research in Sports Medicine, 2008)
The purpose of this study is to examine the epidemiology and trends of body size in college athletics. Data were coded from available athlete rosters from four division 1 college athletic programs for football, basketball, baseball, and men's/women's tennis for the period of 1950 to the present. Data on 17,500 football, 2,470 basketball, 3,868 baseball, 903 men's tennis, and 765 women's tennis athletes were entered. Increases in height, weight, and body mass index (BMI) were seen for all sports at most positions, but the greatest increases were observed in football offensive and defensive linemen. The largest increases in weight and (BMI) were observed amongst football offensive and defensive linemen, placing them at greatest risk for size-related medical complications. Other college sports exhibit increases in height, weight, and BMI as well, but the rates of increase were not as great